The effect of green roof technology and conventional zinc roof to different building materials in tropical climate - Khor, J.A (Universiti Malaysia Sarawak (UNIMAS), 2010)
The aim of this research is to compare and identify the effect of green roof technology and conventional zinc roof to different building materials in tropical climate. Four building models measuring 0.5m×0.5m×0.5m each were built which are, wood and brick models with zinc roof and green roof for each building material respectively. The experiment was carried out by measuring the interior air temperature of each model every hour from 0800h to 1700h for five sunny days. Then, the average temperature for each model was computed. The result has shown that the average temperature differences for the brick material are higher than that for the wood material. For both materials, model with green roof has shown higher temperature compare to model with zinc roof. The results gained were affected by the inconsistency of wind and the cloud appearances during the experimentation period. Besides that, the humidity level in the models and the reflectivity of the zinc roof has caused the temperature of models with zinc roof to decrease.